Gambaran Penerimaan Diri Influencer Gay: Self Acceptance of Gay Influencer - Anidia, Risma; Komalasari, Shanty (Jurnal Al-Husna, 2024)
Self-acceptance is a process when an individual acknowledges, embraces, and understands oneself, including both strengths and weaknesses, as well as unique qualities. For gay individuals, self-acceptance means fully embracing their sexual identity without being concerned about others' perceptions. This study aims to explore the process of self-acceptance in gay individuals who have influence on social media. The theoretical framework utilized is Germer's self-acceptance theory, along with its stages of self-acceptance. The research employs a qualitative approach with interviews as the data collection technique. The interview was conducted with one subject who met the criteria of being a gay individual who has fully accepted themselves and has become an influencer on social media. The results of this study reveal that the subject progressed through all stages of self-acceptance, from avoidance to friendship. The subject chose to become an influencer so that individuals with a gay sexual identity out there could also fully embrace themselves. Keywords: gay; influencer; self acceptance.